An electron-rich small AIEgen as a solid platform for the selective and ultrasensitive on-site visual detection of TNT in the solid, solution and vapor states. Issue 5 (2nd January 2020) - Prusti, Banchhanidhi; Chakravarty, Manab
Abstract : A simple trimethoxybenzene-linked anthracenyl π-conjugate is developed for the ultra-sensitive and selective detection of TNT in solid, liquid and vapor phases. The TNT could also be detected in the field soil. Abstract : Promising research on AIEgen (aggregation-induced emission active fluorogens)-based sensors for the detection of explosives (mostly picric acid) is primarily dominated by polymeric molecules. However, herein, we report the ability of a recently developed anthracene-based electron-rich π-conjugate as a small and suitable AIEgen for the selective and sensitive detection of 2, 4, 6-trinitrotoluene (TNT) through fluorescence (PL) quenching. This fluorophore consists of trimethoxybenzene-linked anthranyl-π-phenothiazine, which is recognized as a significantly electron-rich AIEgen suitable for the selective detection of TNT detection. The detection of TNT was performed in the solid, liquid and vapor states using this AIEgen in the aggregate or solid-state. The detection limit in the solution state was measured to be 3.2 × 10 −9 M. When this fluorophore was impregnated on a paper strip for on-site visual detection, TNT was detected up to the 10 −14 M level by the naked eye using a 365 nm UV-torch. The paper strip was also successfully used to detect TNT in the vapour state. This application was further extended to detect TNT in field soil. The detection of TNT by replacing trimethoxybenzene in the fluorophore with dimethoxy or monomethoxy was a failure, indicating the requirement of an adequate electron-rich system. Unlike the previous report with static quenching as the main reason for TNT detection, our experimental observations demonstrated the participation of favorable photo-induced electron transfer (PET) between TNT and the fluorophore as the origin of the PL quenching.